Biodegradation of pharmaceutical compounds caffeine and carbamazepine using gram-positive bacteria / Najihah Mohamad Nasir - Mohamad Nasir, Najihah (2019)
This study aims to evaluate the potential of selected bacteria in caffeine and carbamazepine degradation. The objectives of this study are to screen potential bacteria in degradation of caffeine and carbamazepine, to optimise degradation parameters of caffeine and carbamazepine as well as to evaluate degrading enzymes for prediction of degradation pathways. Methodologies included screening of bacteria resistance towards caffeine and carbamazepine and optimisation parameters of initial concentrations, initial pH and temperature for degradation of caffeine and carbamazepine. Then, mixed culture study was conducted at the selected optimum condition. At the same time, bacteria growth for Rhodococcus zopfii and Leifsonia shinshuensis was determined to support the degradation result. In addition, enzyme assays for oxygen oxidoreductase, aldehyde oxidase, catechol 1,2 dioxygenase and catechol 2,3 dioxygenase were also conducted. The result demonstrated that bacteria R. zopfii and L. shinshuensis were selected due to growth and potential in utilising caffeine and carbamazepine as nutrient source for degradation. For single culture degradation study, the 10 mgL-1, pH 7 and 40 °C were selected as optimum condition for degradation of caffeine and carbamazepine. Optimum normalised degradation percentage of caffeine by R. zopfii was 72.53 ± 0.10 and L. shinshuensis was only 38.49 ± 0.01. For carbamazepine, both R. zopfii and L.shinshuensis achieved high normalised degradation percentage of 99.99 ± 0.00. Degradation of caffeine was not correlated to bacteria growth meanwhile, degradation of carbamazepine was linearly correlated to the bacteria growth. The result also revealed antagonistic interaction between R. zopfii and L. shinshuensis in mixed culture. Furthermore, enzyme assay for bacteria in caffeine showed presence of enzymes oxygen oxidoreductase and aldehyde oxidase, meanwhile, oxygen oxidoreductase, aldehyde oxidase, catechol 1,2 dioxygenase and catechol 2,3 dioxygenase were determined during carbamazepine degradation.